SAT0708 Symptoms indicative of inflammatory arthritis are common in the primary care population: findings from the symptoms in persons at risk of rheumatoid arthritis survey. (15th June 2017) - Hider, SL; Muller, S; Prior, J; Helliwell, T; Schaardenburg, D van; Mil, A van der Helm-van; Raza, K; Mallen, CD
Abstract : Background: Early, accurate diagnosis of RA is critical to improving outcomes. Patients with RA may develop a variety of symptoms including joint pain, swelling and stiffness. The Symptoms in Persons at Risk of Rheumatoid Arthritis (SPARRA) questionnaire was derived to assess the presence, severity and impact of common symptoms in patients at risk of RA (1). However, to date there is little data available on how common these symptoms are in primary care consulters. Objectives: To describe the prevalence of self-reported inflammatory joint symptoms in primary care patients consulting for both musculoskeletal and non-musculoskeletal complaints. Methods: Questionnaires were sent to 10161 individuals, of whom 5050 had consulted primary care for musculoskeletal problems. The remainder were matched to this sample by age, gender and general practice and had consulted for any non-musculoskeletal indication. Respondents provided data on presence of common symptoms such as joint pain, stiffness and swelling. The prevalence of these symptoms, their severity and impact was compared between musculoskeletal and non-musculoskeletal consulters. Results: 4549 people responded to the survey (adjusted response 45.8%) of whom 52.3% were in the musculoskeletal consultation group. The mean (SD) age was 61.6 (14.8) years and 58.9% were female. Symptoms commonly associated with inflammatory arthritis were common in both groups. 89.1% of musculoskeletal consulters reported current joint pain, compared with 74.9% in the non-MSK consulter group, 48.7% of MSK consulters reported joint swelling compared to 37.3% of non-MSK consulters and 77.9% of MSK consulters reported joint stiffness (64.3% in non-MSK group). A similar proportion in each group reported fatigue (59.5% vs 55%). Joint symptoms remained common symptoms in both groups even when severity and impact of symptoms was considered. Conclusions: Although symptoms such as joint pain, swelling, and stiffness are predictive of inflammatory arthritis, a large proportion of those consulting primary care for non-musculoskeletal reasons routinely report these symptoms when prompted. This compounds the challenges of diagnosing inflammatory arthritis in a non-specialist setting where new approaches are needed to ensure accurate, early diagnosis, facilitating a treat to target approach. References: van Tuyl, et al. Musculoskeletal Care 2016;14:169–73. Acknowledgements: This study represents independent research funded by the National Institute for Health Research (NIHR). TH is funded by a NIHR Clinical Lectureship in General Practice. CDM is funded by the National Institute for Health Research (NIHR) Collaborations for Leadership in Applied Health Research and Care West Midlands, the NIHR School for Primary Care Research and a NIHR Research Professorship in General Practice (NIHR-RP-2014–04–026). The views expressed are those of the authors and not necessarily those of the NHS, NIHR or the Department of Health. Disclosure of Interest: None declared